Persistent Overload Control for Backlogged Machine to Machine Communications in Long Term Evolution Advanced Networks - Dirar, Rofida Osman; Saeed, Rashid. A.; Hasan, Mohammad Kamrul; Mahmud, Musse (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Machine to Machine (M2M) has become one of the most attractive technologies in wireless communications. Despite this, Long Term Evolution Advanced (LTE-A) suffered the severe issues in machines initiating random access for all of the Base Stations (BTS). Therefore, this paper investigated the previous/existing methods and come out with the P-persistent scheme. The scheme is proposed with backlogged M2M devices that use to control Radio Access Network (RAN) overload in LTE-A network. The performance of the proposed scheme is evaluated through MATLAB based simulation. Through the evaluation, it can be seen that the M2M devices arrivals follow Beta distribution use for calculating the throughput and probabilities of collision, success and idle for M2M devices. The first case when P has a high value and the second case P have low value, this result show that in first case the success probability of M2M device is high about 73% limited number of M2M devices and have lower collision probability but in the other case M2M devices have lower success probability about 26% with high collision probability.